The Impact of Inflation and Idr Exchange Rate on Stock Prices In PT Bank Central Asia Which is Already Listed on The Indonesia Stock Exchange - Manap, Abdul (Institute Of Advanced Knowledge and Science, 2025)
This study aims to determine empirical evidence of the Impact of Inflation, Exchange Rates and Interest Rates on Stock Prices. The independent variables used in this study are Exchange Rates, Inflation, and Interest Rates while the dependent variable in this study is Stock Prices. The financial statements used in this study are Bank Central Asia Tbk. The sample used in this study is the stock price of Bank Central Asia listed on the Indonesia Stock Exchange (IDX), with the number of samples from this study being 46 data from 48 data taken in the monthly Bank Central Asia stock price data period from January 2021 to October 2024. The analysis technique used is descriptive statistical analysis and multiple regression analysis as well as hypothesis testing using SPSS 20. This is proven by the results of the H01 hypothesis state that there is no influence of inflation and the IDR exchange rate simultaneously on stock prices. PT Bank Central Asia Tbk, or in other words, inflation and the IDR exchange rate are proven to simultaneously have a significant influence on stock prices. PT Bank Central Asia Tbk